2021
DOI: 10.3389/fonc.2021.546455
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an Individualized Immune-Related Prognostic Risk Score in Lung Squamous Cell Cancer

Abstract: Background: Lung squamous cell carcinoma (LUSC) is one of the most common histological subtypes of non-small cell lung cancer (NSCLC), and its morbidity and mortality are steadily increasing. The purpose of this study was to study the relationship between the immune-related gene (IRGs) profile and the outcome of LUSC in patients by analyzing datasets from The Cancer Genome Atlas (TCGA).Methods: We obtained publicly available LUSC RNA expression data and clinical survival data from The Cancer Genome Atlas (TCGA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 42 publications
(44 reference statements)
0
8
0
Order By: Relevance
“…At present, the gene signal based on abnormal mRNA has been used to predict the prognosis of hepatocellular carcinoma, which has great potential ( 19 , 20 ). Gene signatures based on immune-related genes have been reported in a variety of cancers, such as lung squamous cell cancer, non-small cell lung cancer, esophageal carcinoma, etc ( 13 , 21 , 22 ). In this study, the high-throughput expression profiles of immune-related genes in TCGA-LIHC cohort were analyzed, and the differentially expressed immune genes were screened by differential analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, the gene signal based on abnormal mRNA has been used to predict the prognosis of hepatocellular carcinoma, which has great potential ( 19 , 20 ). Gene signatures based on immune-related genes have been reported in a variety of cancers, such as lung squamous cell cancer, non-small cell lung cancer, esophageal carcinoma, etc ( 13 , 21 , 22 ). In this study, the high-throughput expression profiles of immune-related genes in TCGA-LIHC cohort were analyzed, and the differentially expressed immune genes were screened by differential analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, due to the maturity of high-throughput sequencing technology, a series of changes in tumor tissue genome and normal tissue genome have been excavated. Several studies in different types of cancer, including ovarian cancer, cervical cancer and lung squamous cell cancer (11)(12)(13), immune-related genes were used to establish tumor prognostic models, which further reflects the potential of immune-related genes to become tumor prognostic markers.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, AMH is an immune-related prognostic gene in LUSC and has been used to construct a prognostic model in LUSC [ 31 ]. Zhuang et al also found that AMH is a LUSC-related immune gene and is not associated with distant metastasis [ 32 ]. TWIK-related acid-sensitive potassium channel 1 (TASK1), encoded by KCNK3, is associated with pulmonary circulation and controls pulmonary arterial tone, which may contribute to poor prognosis in lung cancer patients [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…developed TIL-associated IncRNA signature for predicting 3-year OS and yielded an AUC of 0.646 ( 22 ), and Zhuang et al. developed immune gene risk index for predicting 3-year OS with an AUC of 0.666 ( 23 ). However, no individual prognostic models in those study were developed to predict the individualized survival outcomes of NSCLC patients.…”
Section: Discussionmentioning
confidence: 99%